Assessment on Microplastic Contamination from Mulching and Non-Mulching Farmland in Selangor, Malaysia - Zulkarnain, Muhammad Zulfahim; Mohd Yatim, Siti Rohana; Wan Rasdi, Nadiah; Feisal, Nur Azalina Suzianti; Porusia, Mitoriana (Universitas Airlangga, 2025)
Introduction: Emerging environmental contaminants known as microplastics (MPs) have recently attracted a growing amount of attention due to their ubiquitous distribution, high adsorption capability of impurities, high specific surface area, and physiological toxicity, which can remain in the environment for hundreds of years. Thus, this study aimed to characterize microplastics (MPs) and assess their association with varying soil depths and sampling sites, utilizing two distinct plant soil types for comparison. Methods: Soil samples were collected from different depths and various sampling sites within Tanjung Karang, Selangor. The abundance, color, size, shape, and polymer composition of the isolated MPs were analyzed using microscopic techniques and micro-Fourier Transform Infrared (FTIR) spectroscopy. Standard experimental protocols were followed, and one-way ANOVA test was conducted using SPSS. Result and Discussion: Mulched farmland had the most MPs abundance, 1650 particles/kg at 0-10 cm. However, non-mulched farmland had the lowest microplastic abundance at 336 particles/kg at 20-30 cm. This indicates that microplastics were substantially greater in mulched soils than in non-mulched soils. The Stereomicroscope Stemi 305, Zeiss, showed that 64% of films possessed the highest morphotypes, black colour of microplastics made up mostly about 59% of the total, and MPs were the most abundant with a size of <500 μm. ATR-FTIR found mostly polyethylene terephthalate (PET) and polypropylene (PP) polymers in these soils. Also, the abundance of microplastics in both farmlands gradually decreased as the depth of the soil increased. Conclusion: This investigation confirmed that microplastic composition and characteristics vary by agricultural land and soil depth.